Sosialisasi Bahaya Narkoba untuk Remaja di SD Negeri 173632 Porsea - Rivael Sirait; Putra M. Tinambunan; Happy New D. T. Harefa; Eunike Aginta Sinaga; Rahmat S. Silitonga; Parsaoran Silalahi (Jurnal Kemitraan Masyarakat, 2025)
This study aims to analyze the effectiveness of drug socialization on improving adolescent understanding at SDN 173632 Porsea, Toba Regency. Data were collected through questionnaires before and after socialization, which covered various aspects of understanding about drugs. The results showed a significant increase in the accuracy of answers after socialization. Before socialization, the average accuracy of answers was only 74.4%, while after socialization it increased to 99.5%. The most striking increase was seen in the understanding of types of drugs, which was initially only 12.3% to 100%. In addition, understanding of the effects of drugs also increased from 68% to 100%. These results indicate that socialization plays an important role in increasing adolescent awareness and knowledge about the dangers of drugs. Therefore, drug socialization has proven effective in improving adolescent understanding, so that it can help readers, especially teachers and students, in understanding the prevention of drug abuse among students.